Venous thromboembolism after major venous injuries: Competing priorities. Issue 6 (December 2017) - Frank, Brian; Maher, Zoё; Hazelton, Joshua P.; Resnick, Shelby; Dauer, Elizabeth; Goldenberg, Anna; Lubitz, Andrea L.; Smith, Brian P.; Saillant, Noelle N.; Reilly, Patrick M.; Seamon, Mark J.
Abstract : BACKGROUND: Venous thromboembolism (VTE) after major vascular injury (MVI) is particularly challenging because the competing risk of thrombosis and embolization after direct vessel injury must be balanced with risk of bleeding after surgical repair. We hypothesized that venous injuries, repair type, and intraoperative anticoagulation would influence VTE formation after MVI. METHODS: A multi-institution, retrospective cohort study of consecutive MVI patients was conducted at three urban, Level I centers (2005–2013). Patients with MVI of the neck, torso, or proximal extremities (to elbows/knees) were included. Our primary study endpoint was the development of VTE (DVT or pulmonary embolism [PE]). RESULTS: The 435 major vascular injury patients were primarily young (27 years) men (89%) with penetrating (84%) injuries. When patients with (n = 108) and without (n = 327) VTE were compared, we observed no difference in age, mechanism, extremity injury, tourniquet use, orthopedic and spine injuries, damage control, local heparinized saline, or vascular surgery consultation (all p > 0.05). VTE patients had greater Injury Severity Score (ISS) (17 vs. 12), shock indices (1 vs. 0.9), and more torso (58% vs. 35%) and venous (73% vs. 48%) injuries, but less often received systemic intraoperative anticoagulation (39% vs. 53%) or postoperative enoxaparin (47% vs. 61%) prophylaxis (all p < 0.05). After controlling for ISS, hemodynamics, injured vessel, intraoperative anticoagulation, and postoperative prophylaxis, multivariable analysis revealed venous injury was independently predictive of VTE (odds ratio, 2.7; p = 0.002). Multivariable analysis of the venous injuries subset (n = 237) then determined that only delay in starting VTE chemoprophylaxis (odds ratio, 1.3/day; p = 0.013) independently predicted VTE after controlling for ISS, hemodynamics, injured vessel, surgical subspecialty, intraoperative anticoagulation, and postoperative prophylaxis. Overall, 3.4% of venous injury patients developed PE, but PE rates were not related to their operative management ( p = 0.72). CONCLUSION: Patients with major venous injuries are at high risk for VTE, regardless of intraoperative management. Our results support the immediate initiation of postoperative chemoprophylaxis in patients with major venous injuries. LEVEL OF EVIDENCE: Therapeutic/care management, level IV.